Practices of Solidarity and Self-organization in Local Communities - Reutov, Evgenij V.; Reutova, Marina N.; Avilova, Janna N.; Shavyrina, Irina V. (International Review of Management and Marketing, 2016)
Article is devoted to analysis of practices of mutual aid and self-organization, opportunities of their institutional embodiment in social space of local communities. Based on analysis of questionnaire surveys of the population of Belgorod region there were identified the leading motives of cooperation and mutual assistance, which include material deprivation, lack of information resources, the need for confederates, violation of civil rights. The most widely used forms of collective action, based on self-organization are landscaping, collective mutual aid, collective petitions to the authorities. Conducted research enables to draw conclusion of development both vertical and horizontal forms of collaboration and co-operation, at preservation of more significant role of vertical structures. Keywords: local community, self-organization, cooperation, mutual assistance practice, collective action JEL Classifications: D64, D71, R23